PENGARUH PROMOSI, INOVASI PRODUK DAN BRAND REPUTATION TERHADAP KINERJA PEMASARAN (STUDY PADA KEDAI MIE KOBER SINGARAJA) - SUPUTRIYANI, MADE; ASTANA, I GUSTI MADE OKA (GANEC SWARA, 2023)
This research aims to analyze the influence of product innovation promotion and brand reputation on marketing performance (study at the Kober Singaraja noodle shop). In this research, qualitative and quantitative approaches were used in this research. The data collection technique used in this research is using a questionnaire technique using a Likert scale where those selected as respondents were visitors to Mie Kober Singaraja as many as 70 respondents and documentation. This research uses quantitative analysis which is processed using statistics with multiple linear regression analysis, determination analysis, and hypothesis testing using the t test. 1) Based on the results of the Effect of Promotion on Marketing Performance with a value of tcount > ttable (2.992 > 1.984) and a significance value of 0.004, it can be concluded that 0.004 = 0.05 using a significance threshold of 0.05. 2) The influence of product innovation on marketing performance at Mie Kober Singaraja Shop tcount > ttable 4.042 > 1.984 with significance value = 0.00 < 0.05. 3) the influence of Brand Reputation has a positive and significant effect on Marketing Performance at Mie Kober Singaraja Shop with a value of tcount > ttable (3.357 > 1.984) with a significance value of 0.001 < 0.05.